Veracidad de las noticias en las redes sociales (facebook) en el contexto del covid19 – Ecuador periodo marzo-agosto 2020 - Carolina Briggette, Chamba Gonzaga (2022)
Resume during the covid-19 pandemic, great challenges occurred, among them the fight against misinformation generated in social networks due to the lack of verification of sources, which is why the present degree work aims to verify the veracity of the news published on facebook in which no source is cited or, at most, one source about the coronavirus during the period march august 2020. for its scope, a methodology was used with a non-experimental design of a qualitative nature, with an analytical and inductive descriptive method, of a documentary type with descriptive, exploratory depth; in the same way it is qualitative in nature. according to the result obtained, 256 news items published on the fan page of each medium were analyzed, allowing us to identify whether or not there was truthfulness during the writing of the news in times of covid-19. finally, based on the results obtained from the investigation, it was recognized that the sources of the news should be verified, however on the internet they are not governed by that principle for their publication, either because of the immediacy issue. in which the need to report at the moment is fought against without taking the necessary space to verify, increasingly normalizing the omission of steps to counteract the facts, taking into account that the broadcast media and traditional media lose trust and above all the credibility of the citizens. keywords: truthfulness, social networks, facebook, covid-19